2021
DOI: 10.3390/math9040355
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Approach to the Adoption Process of Bitcoin by Business Executives

Abstract: The purpose of this research study is to analyze the exploratory study of the adoption of Bitcoin cryptocurrency based on blockchain technology and its use as a means of payment in companies. This research is exploratory in nature. As such, an adoption model was investigated using the technology acceptance model (TAM) which was extended with new variables. The sample was made up of business executives from companies and commercial establishments (n = 248). Partial least squares structural equation modeling (PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
3
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 106 publications
(168 reference statements)
3
49
3
4
Order By: Relevance
“…Such opportunities are currently associated with their fast adoption by ordinary people and other organizations. Adoption by companies is also supported by the fact that the number of corporations using cryptocurrency for payment is constantly increasing [64]. The cryptocurrency technology is currently undergoing the experimentation phase, or limitedscale production [65].…”
Section: Main Conclusion For Practicementioning
confidence: 99%
“…Such opportunities are currently associated with their fast adoption by ordinary people and other organizations. Adoption by companies is also supported by the fact that the number of corporations using cryptocurrency for payment is constantly increasing [64]. The cryptocurrency technology is currently undergoing the experimentation phase, or limitedscale production [65].…”
Section: Main Conclusion For Practicementioning
confidence: 99%
“…In years 2017 and 2018, only one article is relevant according to research criteria, whereas in 2019, it increases to six, and in 2020, it is 19, which shows an upward trend. Previous studies done in the different fields of blockchain technology have also reported that blockchain technology is gaining attention and the number of publications is showing an upward trend (Pal et al , 2021; Rejeb et al , 2021; Cagigas et al , 2021). The interest of researchers, academicians and policymakers toward blockchain adoption is increasing.…”
Section: Resultsmentioning
confidence: 98%
“…The journals are from multidisciplinary fields, which show that the blockchain technology adoption is a multidisciplinary area of research. Previous studies reported that the studies done on blockchain technology are dispersed and published in journals from multidisciplinary area (Pal et al , 2021; Cagigas et al , 2021; Tandon et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Todavia, apesar do presente estudo ter identificado que a dimensão Utilidade possui relação positiva com a atitude em utilizar criptomoedas por gestores de empreendimentos turísticos, a relação entre "Utilidade percebida" e "Intenção de uso" (H2) não obteve confirmação, tendo sua hipótese rejeitada. Em outras palavras, significa que existe uma relação de mediação entre utilidade e atitude no efeito de intenção de uso de criptomoedas (Palos-Sanchez et al, 2021), porém não existe relação direta entre as dimensões Utilidade percebida e Intenção de uso, mesmo que outros estudos anteriores a tenham corroborado (Yeong et al, 2019;Cordero, Sánchez, & Cortés, 2020;Nuryyev, Wang, Achyldurdyyeva, et al, 2020). Dessa maneira, os resultados mostraram que os gestores podem até possuir uma avaliação positiva da utilidade das criptomoedas como forma de pagamento, porém essa utilidade não influencia diretamente na sua intenção de uso.…”
Section: R2 = 091unclassified